DOES ALDOSTERONE VIA MINERALOCORTICOID RECEPTORS AND ENAC PROMOTE INTERLEUKIN-17 PRODUCTION IN LYMPHOCYTES?. (April 2021) - Thangaraj, Sai Sindhu; Oxlund, Christina; Mortensen, Line Aas; Thiesson, Helle; Abildgaard, Ib; Jensen, Boye
Abstract : Objective: Despite availability of antihypertensive therapeutic strategies, 20% of hypertensive patients remain resistant towards conventional treatment. Studies have shown that interleukin 17 (IL-17) from Th17 lymphocytes may be an important factor in the pathophysiology of hypertension. IL-17 plasma concentration is increased in hypertensive type 2 diabetes (T2D) patients compared to non-hypertensive diabetes patients. In vitro studies have shown the epithelial sodium channel ENaC to be expressed in lymphocytes. Activation of the mineralocorticoid receptor (MR) promotes pro-inflammatory Th17 lymphocyte differentiation in a spironolactone-sensitive way. We therefore hypothesized that aldosterone and ENaC may promote IL-17 production in lymphocytes ex vivo and from T2D hypertensive and kidney transplant patients in vivo. Design and method: Treatment resistant hypertensive T2D patients were included in a randomized double blinded study where patients were allocated to receive either spironolactone or placebo for 16 weeks (n = 116). After a two-week wash-out period the patients were included in an open label non-controlled follow-up study receiving amiloride for 8 weeks (n = 60). In a third randomized double blinded study, kidney transplant patients were allocated to receive either placebo or spironolactone for 1 year (n = 80). Plasma samples were available from all trials before and after intervention. Key cytokines involved in Th17 differentiation (IL-17, IL-6, IL-1β, IL-10, IFN-γ, TNF-α) were measured in plasma samples from the three interventional studies using ELISAs from Mesoscale. Results: Spironolactone intervention in T2D hypertensive patients lead to a decrease in plasma IFN-γ and IL-6. Amiloride intervention in the same patient group showed with a decrease in plasma IL-6 and TNF-α and an increase in IL-10 levels Conclusions: Spironolactone and amiloride treatment of hypertensive and kidney transplant patients had no effect on IL-17 concentrations in plasma. Spironolactone suppressed the cytokines IFN-γ and IL-6, whereas amiloride decreased the levels of IL-6 and TNF-α and cause an increase in the anti-inflammatory cytokine IL-10. Since these are key cytokines of macrophage activation, MR and ENaC may be relevant for monocyte-macrophage activation. Future ex vivo experiments will be performed to elucidate the effect of amiloride and spironolactone on cytokine release from Th17 cells and macrophages.